Halliburton's army : how a well-connected Texas oil company revolutionized the way America makes war - Chatterjee, Pratap (New York : Nation Books, 2009)
Examines the role of the oil company in conflicts around the world such as the Iraq War, and its questionable dealings with government officials, special contracts, bribes, offshore subsidiares, and the U.S. military.
Introduction: A revolution in military affairs -- Riding the catfish to Anaconda -- Early days of Brown & Root -- Brothers in arms : Dick Cheney and Donald Rumsfeld -- Cheney at the helm -- The birth of LOGCAP -- Supporting the War on Terror -- Operation Restore Iraqi Oil (RIO) -- Corruption in Kuwait -- Camp Anaconda -- Keep on truckin' -- The whistle-blowers -- Investigation and punishment -- Conclusion: Revisiting the revolution in military affairs.
Keywords: Halliburton Company -- History; Petroleum products -- Texas -- History